Il mercato del vino nella Grande Distribuzione Organizzata in Italia Tendenze 2009-2017 e previsioni - Fabbrizzi, Sara (Proceedings e report, 2020)
This report analyzes the composition and trends of wine sales in the Italian large-scale retail trade in the period 2009-2017. The analysis focuses on wine sales by type of product, i.e. sales format, color, still/sparkling wine, geographical indication, sales in promotion. Specific insights regard wines in 0.75 liter glass bottles, Private Label wine and the first twenty designations of origin in terms of value sold in the large-scale distribution. Lastly, forecasting models based on quarterly time series have been developed to provide a picture of the future performance of the sector. The study allows defining appropriate strategies to be implemented to respond to new consumption trends.